Tinjauan Atas Asas Keadilan dan Kemudahan Administrasi Pajak dalamPengenaan Pajak Penghasilan Final 1% Terhadap Wajib Pajak UMKM - Arianty, Fitria (UI Scholars Hub, 2017)
The purpose of Final Tax Policy for SMEs is to increase tax revenue from the SMEs sector, which is classified as an underground economy activities because of their economy activity is not detected by conventional tax collection system. The application of this Final Tax Policy emphasizes The Principle Ease of Tax Administration ignoring The Principle of Equity, so that SMEs are included in the database Taxpayers Directorate General of Taxation, to then be able to carry out their tax liability. The research method is descriptive qualitative approach. The data obtained are primary and secondary data that can be used as a review and foundation researcher to analyze the problems that exist. Results of research and analysis that has been done is that researchers at the Tax Administration Ease of implementation principle put forward by policymakers do not fully achieved, the policy raises additional final income tax administrative burden for taxpayers who are subject to this policy.